The Neurological and Neurosurgical Presentations of SARSCoV2 Affected Patients: A Systematic Review. - Selina, Farhana; Talha, Khandaker Abu; Ahmed, Mostafa Taufiq; Karim, Ishrat Jahan; Nasir, Morshed; Latif, Sonia; Perveen, Rawshan Ara; Bhattacharya, Ramanuj (Bangladesh Journal of Neurosurgery, 2021)
Presentation with neurological complaint is not very uncommon. Few patients report with intracerebral hemorrhage which are considered as cases of neurosurgical intervention, on the other hand respiratory depression and encephalitis patients need care in Neurosurgical intensive care unit (Neurosurgical ICU) for treating or measuring intracranial pressure (ICP). This systematic review includes 2683 COVID- 19 patients of 17 articles who had neurological manifestations. Out of these 17 studies 8 articles were retrospective case series, 3 were prospective case series, 3 were case reports, 2 were cross-sectional and 1 cohort study. Headache was commonest neurological feature presented in 7 studies. Cerebro-vascular problem, loss of smell and impaired conscious level was present in four studies each. Seizure was presenting feature in 3 studies. There were series where patients reported with loss of taste. Other presenting features were dizziness and ataxia. Previous studies supported that Corona virus can cause encephalitis, multiple sclerosis or cerebral hemorrhage. Respiratory failure due to damage of cardiorespiratory center of brainstem by COVID- 19 virus has not been ruled out. Bang. J Neurosurgery 2021; 10(2): 169-174